2022
DOI: 10.1021/acsanm.1c04417
|View full text |Cite
|
Sign up to set email alerts
|

Modified Outer Membrane Protein-G Nanopores with Expanded and Truncated β-Hairpins for Recognition of Double-Stranded DNA

Abstract: The detection of single molecules such as singlestranded DNA (ssDNA) and other small molecules through biological nanopores is a powerful approach for analyzing DNA sequences and DNA shapes, as well as for disease diagnostics. The fixed diameter of biological nanopores restricts the size of biomolecules translocated through them. Although some nanopores such as ClyA, FraC, Phi29p, and γ-hemolysin have been shown to translocate double-stranded DNA (dsDNA), identifying the difference between dsDNA and three-way … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(13 citation statements)
references
References 50 publications
1
12
0
Order By: Relevance
“…To investigate K + transport properties of a single bpy-AmB channel in the presence of transition metal ions (Cu 2+ , Co 2+ , or Ni 2+ ions), we recorded a single current signal of bpy-AmB in the planar lipid bilayer using an on-chip lipid bilayer system. , First, to confirm channel formation of bpy-AmB, the single current signal of bpy-AmB on a planar DPhPC bilayer containing 5 mol % ergosterol (5 mol % Ergo/DPhPC) was observed in 3 M KCl containing 2.5 mM HEPES and 1 mM CaCl 2 (pH 9.0) at +150 mV. Figure S5a shows an open-close signal of bpy-AmB.…”
Section: Resultsmentioning
confidence: 99%
“…To investigate K + transport properties of a single bpy-AmB channel in the presence of transition metal ions (Cu 2+ , Co 2+ , or Ni 2+ ions), we recorded a single current signal of bpy-AmB in the planar lipid bilayer using an on-chip lipid bilayer system. , First, to confirm channel formation of bpy-AmB, the single current signal of bpy-AmB on a planar DPhPC bilayer containing 5 mol % ergosterol (5 mol % Ergo/DPhPC) was observed in 3 M KCl containing 2.5 mM HEPES and 1 mM CaCl 2 (pH 9.0) at +150 mV. Figure S5a shows an open-close signal of bpy-AmB.…”
Section: Resultsmentioning
confidence: 99%
“…Recently, the conversion of the pore diameter has been reported by duplicating or replacing one or several β-hairpins of β−barrel nanopores, such as LamB, FhuA, and OmpX [ 139 , 140 , 141 ]. OmpG mutants with different numbers of β-hairpins showed that the pore diameter and ion current amplitude depend on the number of β-hairpins and the balance of charged amino acids on the inner surface of the OmpG nanopore [ 142 ]. Additionally, the R. Kawano group designed de novo nanopores formed by β−barrels and investigated the formation mechanism and ion transport properties of the nanopore using BLM systems and MD simulation [ 143 ].…”
Section: Single-channel Recording Using Planar Bilayer Lipid Membrane...mentioning
confidence: 99%
“…In 2016, the application of this technique was commercialized as a DNA sequencer by Oxford Nanopore Technologies. Single-molecule detection techniques, such as DNA, RNA, and small organic molecules, have been reported using aerolysin (AeL) [ 145 , 146 , 147 ], fragaceatoxin C (FraC) [ 148 , 149 ], OmpG [ 142 , 150 ], and FhuA [ 151 , 152 ] ( Figure 6 a–d). Recently, the development of peptide sequencing techniques using protein nanopores, such as AeL, Mycobacterium smegmatis porin A (MspA), and proteasome-nanopore, has been reported [ 153 , 154 , 155 ].…”
Section: Single-channel Recording Using Planar Bilayer Lipid Membrane...mentioning
confidence: 99%
See 1 more Smart Citation
“…Proteo-GUVs prepared using our method contain buffer and lipid components that are suitable for the functions of each membrane protein. In this study, we sought to evaluate molecular transport on GUVs and a bilayer lipid membrane (BLM) integrated with a β-barrel porin and outer membrane protein G (OmpG), which is applied to biological sensors for the detection of small molecules, such as peptides and adenosine triphosphate. To the best of our knowledge, the formation of OmpG-GUV has not been reported. The reconstitution of Omps into GUV is difficult because the folding of Omps in the cell membrane is catalyzed by the β-barrel assembly machinery complex in Gram-negative bacteria. , Our reconstitution method can be one of the proteo-GUV formation methods in Omps that are difficult to reconstitute into GUV by other methods.…”
Section: Introductionmentioning
confidence: 99%